The Role of Inflammation and Immune Cells in Blood Flow Restriction Training Adaptation: A Review - Rossi, Fabrício Eduardo; de Freitas, Marcelo Conrado; Zanchi, Nelo Eidy; Lira, Fábio Santos; Cholewa, Jason M. (Frontiers in Physiology, 2018)
Blood flow restriction (BFR) combined with low-intensity strength training has been shown to increase skeletal muscle mass and strength in a variety of populations. BFR results in a robust metabolic stress which is hypothesized to induce muscle growth via increased recruitment of fast-twitch muscle fibers, a greater endocrine response, and/or enhancing the cellular swelling contribution to the hypertrophic process. Following exercise, neutrophils are the first immune cells to initiate the tissue remodeling process via several mechanisms including an increased production of cytokines and recruitment of monocytes/macrophages, which facilitate the phagocytosis of foreign particles, the differentiation of myoblasts, and the formation of new myotubes. Thus, the purpose of this review was to discuss the mechanisms through which metabolic stress and immune cell recruitment may induce skeletal muscle remodeling following BFR strength training.